Interactions between Halothiobacillus neapolitanus and mortars: Comparison of the biodeterioration between Portland cement and calcium aluminate cement. (July 2017) - Lors, Christine; Hondjuila Miokono, Eminence Dorelle; Damidot, Denis
Abstract: Biodeterioration of mortars made either with ordinary Portland cement or calcium aluminate cement by Halothiobacillus neapolitanus was investigated by bioleaching experiments. Mortar deterioration, determined by a leaching coefficient calculated with the amounts of chemical elements leached from the mortar to the bacterial suspension, was greater for ordinary Portland cement. The amount of biogenerated sulfuric acid, estimated by the consumption of sulfur-containing components, varied markedly due to the interactions between H. neapolitanus and the mortar that depended on two main mechanisms. First, the different mineralogy of both cement pastes led to a weaker acid-neutralizing capacity of calcium aluminate cement in the pH range 6.5 to 3. Second, a restricted oxidation of tetrathionate by H. neapolitanus, that limited the biogeneration of sulfuric acid, was observed when pH approached 3 more rapidly. Consequently, the weaker acid-neutralizing capacity of calcium aluminate cement induced a quicker drop of the pH of the bacterial suspension from 6.5 to 3, leading to a decrease of the amount of biogenerated sulfuric acid. Thus, calcium aluminate cement mortar in the presence of H. neapolitanus bacterial suspension was less deteriorated than ordinary Portland cement mortar in the pH range considered. Graphical abstract: Highlights: Monitoring bacterial activity is essential to compare bioleaching assays. Better performance of CAC mortar is related to its weaker acid-neutralizing capacity. Weaker acid-neutralizing capacity induces a quicker drop of pH from 6.5 to 3. A quicker drop of pH limits the oxidation of tetrathionate by H. neapolitanus. Limited oxidation of tetrathionate reduces the amount of biogenerated sulfuric acid.